The Application of the EDAS Method in the Parametric Selection Scheme for Maintenance Plans in the Nigerian Food Industry - Victor Chidiebere Maduekwe; Sunday Ayoola Oke (Jurnal Rekayasa Sistem Industri, 2022)
Nowadays, maintenance performance in organizations has become compelling due to competitiveness in the global market and the inclusion of more legislation issues (such as safety and health regulations) in assessments. In this article, the purpose is to formulate in maintenance problem for a food processing unit as a multicriteria problem and solve it using the evaluation based on distance from the average solution (EDAS) method. To attain this purpose, the authors defined a set of weighted criteria and a set of alternatives, and the solution is the alternative that scores the best in those criteria. Consequently, analysis was done based on the EDAS method and the calculated results from the literature data. Consequently, the parameters considered include the frequency of failure, MTBF, MTTF and MTTR while availability is the response. The EDAS method was used to select the best alternative (MTTR, 0.8802) and this score of 0.8802 is for an alternative. The chief novelty of this article is the unique introduction of an innovative EDAS method, which requires only two measures of the desirability of alternative (positive and negative distances from the average solution) but excluded the evaluation of the idea and nadir solutions for the key performance indicators of maintenance. Consequently, this study initiates a maintenance plan for the food industry referring to the key performance indicators as a cause for poor availability of equipment in the Nigerian food industry.